Achieving Shared Prosperity in Kenya - World Bank (Washington, DC, 2014)
This book is organized around three overarching themes under which various topics are aggregated. The first concerns human development and resilience, and discusses issues related to poverty, education, health and social safety nets. This is the human chapter, dealing with crucial areas that are central for the successful development of individual Kenyans. The second theme, growth and competitiveness, delves into the structural issues that need attention for the economy to grow and become more competitive in the international scene. This section of the book discusses needs for infrastructure investments and energy development, along with steps Kenya needs to take to unleash its export potential. The third theme, governance, addresses issues around strengthening public financial management, improving transparency and accountability, and consolidating judicial reform.